The capsalidae (Monogenea: Monopisthocotylea): a review of diversity, classification and phylogeny with a note about species complexes - Whittington, Ian D (Folia parasitologica, 2004)
The Capsalidae are monogeneans parasitizing 'skin', fins and gills of marine fishes. Some capsalids are pathogenic to cultivated fish and a few have caused epizootic events. It is a cosmopolitan family with broad host associations (elasmobranchs and teleosts, including sturgeons). Approximately 200 capsalid species are placed in nine subfamilies and 44-46 genera, some of which are well known (Benedenia, Capsala, Entobdella, Neobenedenia). Sturgeons host two capsalid species (Nitzschiinae) and 15 species in five genera are reliably reported from elasmobranchs. The combination of ancient (shark, ray, sturgeon) and modem (teleost) host fish lineages indicates that capsalid evolution is likely a blend of coevolution and host-switching, but a family phylogeny has been lacking due to deficient knowledge about homologies. The current phenetic subfamilial classification is discussed in detail using a preliminary phylogeny generated from large subunit ribosomal DNA sequence data from representatives of five subfamilies. Monophyly of the Capsalidae is supported by possession of accessory sclerites. Hypotheses are proposed for the possible radiation of capsalids. A suggestion that Neobenedenia melleni, a pathogenic species atypical due to its broad host-specificity (>100 host teleost species from >30 families in five orders), may be a complex of species is supported from genetic evidence. This may explain peculiarities in biology, taxonomy, host associations and geographic distribution of N. 'melleni' and has implications for fish health. Holistic studies using live and preserved larval and adult capsalid specimens and material for genetic analysis are emphasised to further determine identity, phylogeny and details of biology, especially for pathogenic species.
Keywords: ploštěnci; Species Specificity; ribozomální DNA; Fishes; Animals; Platyhelminths; biodiverzita; druhová specificita; DNA, Ribosomal; Phylogeny; zvířata; fylogeneze; ryby; Biodiversity